Genetic diversity and effect of salinity on Morpho-physiochemical properties of purslane (Portulaca oleracea L.) germplasm collections - Alam, Md. Amirul (2014)
Global warming is already having significant and costly effects on our climate, our health, our environment and overall agricultural system. Global warming is also accelerating the rate of sea level rise, increasing flooding risks to low-lying communities, high-risk coastal properties, causing severe salinity and making agricultural land unsuitable for crop production. Considering such situation environmental friendly technologies with stress tolerant crop species is the only solution for sustainable agricultural development. Purslane (Portulaca oleracea L.) is a pioneer vegetable crops having moderate to high salt tolerant capability containing vitamins and minerals and rich in antioxidant properties than any other vegetable crops ever reported. The present study was therefore designed to select high salt tolerant purslane accessions and their morpho-physiological variation due to salinity stress as well as impact on antioxidant properties. A survey was conducted to collect available purslane accessions from seven states (Selangor, Melaka, Negeri Sembilan, Kedah, Perak, Penang and Perlis) of Western Peninsular Malaysia. A total of 45 purslane samples were collected and divided into seven different groups based on distinct morphological variation. Morpho-physiological and mineral variations were also evaluated among collected purslane accessions. Highly significant variations were observed among accessions as well as measured parameters. Variations were also recorded among the same groups may be due to collection from different location. Twenty eight ISSR and ten EST-SSR markers based genetic diversity analysis was carried out among collected purslane germplasms. Analysis of molecular variance (AMOVA) showed 89% and 71.87% variation within the populations while variation among the populations accounted for 11% and 28.13% using ISSR and ESTSSR markers respectively. A dendrogram was constructed by Unweighted Pair Group Method with Arithmetic Average (UPGMA) based on Nei’s genetic distance grouped the whole germplasms into 7 and 8 distinct clusters respectively from ISSR and ESTSSR markers. Based on the information from this dendrogram, accessions that are far from each other by virtue of genetic origin and diversity index are strongly recommended to be used as parent for improved variety development. Another glass house experiment was conducted with initially selected 25 purslane accessions and subjected to five salinity (0.0, 10.0, 20.0, 30.0 and 40.0 dS m-1 NaCl) treatments to screen out high salt tolerant purslane accessions. Overall salinity effect on morphology and reduction of dry matter content of two accessions were graded as tolerant (Ac7 and Ac9), six accessions were moderately tolerant (Ac3, Ac5, Ac6, Ac10, Ac11 and Ac12) and five accessions were moderately susceptible (Ac1, Ac2, Ac4, Ac8 and Ac13) for biomass production and the rest 12 accessions were susceptible to high salinity (30.0 and 40.0 dS m-1 NaCl) and discarded from the further research program. The results also revealed that ornamental purslane were more salt tolerant over common purslane. The selected 13 purslane accessions were again subjected to five (0.0, 8.0, 16.0, 24.0 and 32.0 dS m-1 NaCl) salinity levels to determine the effect of salinity on detailed morphological, physiological, minerals, antioxidant properties and on stem-root histology of purslane. At the highest (30 dS m-1) salinity significant reduction was observed for morphological traits but for physiology, increase in chlorophyll content was seen in Ac2, Ac4, Ac6 and Ac8 at 16 dS m-1 salinity. Whereas, Ac4, Ac9 and Ac12 showed increased photosynthesis activity at the same salinity levels compared to control. Anatomically, stem cortical tissues of Ac5, Ac9 and Ac12 were unaffected at 8 dS m-1 salinity but root cortical tissues did not show any significant damages except a very small enlargement in Ac12 and Ac13. In general Ac9, an ornamental purslane was the best salt tolerant accession, while Ac13 a common purslane was the most affected accession. Regarding antioxidant properties on average over all accessions, different levels of salinity treatment resulted in 8-35% increases in TPC; about 35% increase in TFC; and 18-35% increases in FRAP activity. In contrast, at the lower salinity levels (8 and 16 dS m-1) all the measured minerals found to increase but observed to decrease later with increasing of salinity, but performance of different accessions were different depending on salinity levels. Salinity treatment experiments conducted in our study followed by investigation of different morpho-physicochemical and antioxidant attributes of purslane are valuable for the selection of best salt-tolerant accessions with optimum yield and productivity and antioxidant nutrients. Based upon the data generated such accessions can thus be recommended for cultivation in the saline areas of Malaysia to benefitting health of consumers and as well as sustainable and beneficial utilization of the lands.